Comparison of sprint stride kinematics between three different carbon spikes - a case study - van den Tillaar, R. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The aim of this study was to compare the effect of three different carbon spikes that have different carbon plate and foam placement upon stride-by-stride kinematics during short and long sprints. An international leveled 400m (52.60 s) master athlete performed several 50 and 200m sprints, while wearing three different carbon spikes types in which stride kinematics and angular foot velocity were measured. The main findings were that in the 50m sprints with Puma spikes peak velocity and step frequency were lower with longer contact times than with the other spikes and during the 200m Saucony had a shorter average step length than Adidas. The largest changes in kinematics were found in the angular foot velocities in both sprints thereby it was concluded that placement of carbon plate can influence step kinematics particularly during the short sprint for this athlete.